2010
DOI: 10.1007/s10661-010-1432-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of heavy metal pollution in seawater of Kepez harbor of Canakkale (Turkey)

Abstract: In this work, the heavy metals cadmium and lead in Kepez harbor were studied with regard to the determination of the environmental pollution levels. Seawater samples of the Dardanelles (Canakkale Strait) were collected from the nearest station to Kepez harbor in July 2007. Then, the concentrations of these metals were determined after simple pretreatment of samples by the proposed inductively coupled plasma-atomic emission spectrometry (ICP-AES) method. The analysis of a given sample is completed in about 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Apart from stochastic sampling errors, a possible explanation of this phenomenon could be the heavy environmental pollution in these areas. Indeed, the levels of water pollution in the marine area of Canakkale exceed the limit values according to the World Health Organization (WHO) and the Environmental Protection Agency (EPA), mainly due to the deposition of approximately 280 tons cadmium and 4500 tons lead reaching the Dardanelles from the Danube River (Yilmaz and Sadikoglu, 2011). Similarly, approximately 120,000-150,000 tons of municipal wastewater are deposited daily in the marine area of Kalochori via a pipe (Karvelas et al, 2003).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Apart from stochastic sampling errors, a possible explanation of this phenomenon could be the heavy environmental pollution in these areas. Indeed, the levels of water pollution in the marine area of Canakkale exceed the limit values according to the World Health Organization (WHO) and the Environmental Protection Agency (EPA), mainly due to the deposition of approximately 280 tons cadmium and 4500 tons lead reaching the Dardanelles from the Danube River (Yilmaz and Sadikoglu, 2011). Similarly, approximately 120,000-150,000 tons of municipal wastewater are deposited daily in the marine area of Kalochori via a pipe (Karvelas et al, 2003).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…The toxicity of heavy metals has long been a concern since it is very important to the health of people and ecology. Human activities such as industrial and municipal effluents, as well as atmospheric deposition, geologic weathering, and agricultural activities are the main sources of metals in rivers (Yilmaz and Sadikoglu 2010;Dragun et al 2009;Sanayei et al 2009;Li et al 2008) The existence of heavy metals in aquatic environments has led to serious concerns about their influence on plant and animal life. Metal nutritional requirements (Cu, Zn, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Hence, trace metals may be sensitive indicators for monitoring changes in the water environment. Rivers are dominant pathways for metals transport (Miller et al 2003) and trace metals may become significant pollutants of many river estuarine systems (Sundaray 2010;Yilmaz and Sadikoglu 2010;Wang et al 2010;Suratman et al 2009). The Mahanadi River system is the third largest in the peninsula of India and the largest river in the state of Orissa.…”
Section: Introductionmentioning
confidence: 99%
“…Seawater heavy metal concentrations in samples from the Honghai Bay [20] and Yangtze River estuary [21], China, were much lower than those found in the present study, with concentrations of Cd, Hg, Pb, and Zn being an order of magnitude lower. In a study conducted in Kepez Harbor (Canakkale, Turkey) [23], levels of Cd and Pb were extremely high. The Cd concentration was much lower, whereas concentrations of Cu, Pb, and Zn were markedly higher in comparison with the present study.…”
Section: Distribution Of Heavy Metalsmentioning
confidence: 99%
“…Concentrations of different metals reported in the Bohai Bay, China [22], displayed marked variation. Comparison with preconstruction levels indicated that the Cd and Pb pollution was the result of construction of the Kepez Harbor facilities [23]. In a study conducted in Kepez Harbor (Canakkale, Turkey) [23], levels of Cd and Pb were extremely high.…”
Section: Distribution Of Heavy Metalsmentioning
confidence: 99%